Comparison of Two Respiratory Support Strategies for Stabilization of Very Preterm Infants at Birth: A Matched-Pairs Analysis - Martherus, Tessa; Oberthuer, André; Dekker, Janneke; Kirchgaessner, Christoph; van Geloven, Nan; Hooper, Stuart B.; Kribs, Angela; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Objective: Respiratory support for stabilizing very preterm infants at birth varies between centers. We retrospectively compared two strategies that involved either increasing continuous positive airway pressures (CPAP), or increasing oxygen supplementation. Methods: Matched-pairs of infants (<28 weeks of gestation) were born either at the Leiden University Medical Center [low-pressure: CPAP 5–8 cmH2O and/or positive pressure ventilation (PPV) and fraction of inspired oxygen (FiO2) 0.3–1.0; n = 27], or at the University Hospital of Cologne (high-pressure: CPAP 12–35 cmH2O, no PPV and FiO2 0.3–0.4; n = 27). Respiratory support was initiated non-invasively via facemask at both units. Infants (n = 54) were matched between centers for gestational age and birth weight, to compare physiological and short-term clinical outcomes. Results: In the low-pressure group, 20/27 (74%) infants received 1–2 sustained inflations (20, 25 cm H2O) and 22/27 (81%) received PPV (1:19–3:01 min) using pressures of 25–27 cm H2O. Within 3 min of birth [median (IQR)], mean airway pressures [12 (6–15) vs. 19 (16–23) cmH2O, p < 0.001] and FiO2 [0.30 (0.28–0.31) vs. 0.22 (0.21–0.30), p < 0.001] were different in low- vs. high-pressure groups, respectively. SpO2 and heart rates were similar. After 3 min, higher FiO2 levels [0.62 (0.35–0.98) vs. 0.28 (0.22–0.38), p = 0.005] produced higher SpO2 levels [77 (50–92) vs. 53 (42–69)%, p < 0.001] in the low-pressure group, but SpO2/FiO2 and heart rates were similar. While intubation rates during admission were significantly different (70 vs. 30%, p = 0.013), pneumothorax rates (4 vs. 19%, p = 0.125) and the occurrence of spontaneous intestinal perforations (0 vs. 15%, p = 0.125) were similar between groups. Conclusion: Infants (<28 weeks) can be supported non-invasively at birth with either higher or lower pressures and while higher-pressure support may require less oxygen, it does not eliminate the need for oxygen supplementation. Future studies need to examine the effect of high pressures and pressure titration in the delivery room.